A Case Report of Carbimazole Induced Agranulocytosis - Mariya, Anns; R, Sreenath; Maria, Dona (Indian Journal of Pharmacy Practice)
Carbimazole is an antithyroid medication used to treat an overactive thyroid gland. Agranulocytosis is a rare but potentially serious adverse effect that cannot be predicted by routine measurement of white blood cell count but which is reversible on stopping treatment. Patients should be warned to stop the drug and seek medical advice immediately, if severe sore throat, infections or fever develop while on treatment. Here a 52-year-old female patient was admitted with complaints of painful swelling in the scalp, neck and right hand. She was hyperthyroid and taking neomercazole 10 mg twice daily. Laboratory examination shows the possibility of carbimazole induced agranulocytosis. The drug was stopped, and with the treatment she received, her counts gradually showed an improving trend and she was discharged.
Keywords: Carbimazole; Agranulocytosis; Colony stimulating factor; Infections